Wave emission from an open-ended cylindrical channel in a cold magnetoplasma. - Kudrin, A.V (IEEE Transactions on antennas and propagation)
We study wave emission from a transmitting system consisting of a magnetic-field-aligned cylindrical plasma channel of enhanced density and a loop antenna immersed in it. An ambient medium is assumed to be a cold uniform magnetoplasma. It is found that when the plasma density in the near-antenna zone increases, the total power radiated from the antenna increases considerably due to the efficient excitation of guided modes on the channel. We consider the emission of these modes from the channel end, assuming that the plasma density in the channel decreases gradually with distance from the loop. It is shown that under ionospheric conditions this transmitting system can be useful for improving the antenna coupling to VLF waves of the ambient plasma